Quality of English Textbook Work in Progress for SMA/SMK/MA Class X in Edition 2022: A Content Analysis - Fitria, Tira Nur (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah, IAIN Kediri, 2024)
This research describes the quality of an English textbook “Work in Progress” for SMA/SMK/MA Class X, especially edition 2022. This research is content analysis. The analysis shows that the book consists of chapters, the topic of the chapter, instructional objectives, questions to think about, tasks (project), chapter review, enrichment, reflection, and assessment. The Theory of Quality book by Greene & Petty (1971), this book has good quality based on ten criteria including 1) attracting the students’ interest through games such as Bingo and board games. 2) motivating students by using audiovisuals (photos/videos) and doing the design project. 3) loading/containing interesting illustrations in cartoon/caricature. 4) considering linguistic aspects and telling about English skills including listening, speaking, reading, writing, vocabulary, grammar, and structures. 5) connecting to other subjects, such as related to subjects of sports, psychology (mental health), health, and nutrition. 6) stimulating students' activity, especially in doing individual tasks/projects. 7) Avoid vague concepts and use clear concepts, especially in instructions to do something based on the pictures given. 8) having a clear point of view, especially in the second-person point of view. 9) emphasizing the moral values to students/readers such as containing the story of Malin Kundang and Little Red Riding Hood. 10) respecting and appreciating the student's personality. The textbook is appropriate and suitable for its users (high school students). In terms of language, the book is communicative, easily understood by students, and does not contain a provocateur or anything like that.